Réponses

Meilleure réponse !
2013-01-16T18:58:35+01:00

Bonjour,

 

a)22x² + 25x + 4 = (5x + 2)² - 3x² + 5x =

 

22x² + 25x + 4 = 25x²+20x+4 - 3x² + 5x =

 

22x² + 25x + 4 = 22x² + 25x + 4

 

 

b) (x + 5)(3x -2) + (x +5)(5x - 4 ) = (x + 5)(8x-6)

 

(x + 5)(3x -2+5x - 4 ) = (x + 5)(8x-6)

 

(x + 5)(8x -6) = (x + 5)(8x-6)

 

 

 

c) (5x + 8)² -4(2x + 5 )² = (3x - 6)(3x + 6)

 

(5x+8+2(2x + 5 ))((5x+8-2(2x + 5 ))=

 

(5x+8+4x+10)(5x+8-4x-10) =

 

(9x+18)(x-2) =

 

3(3x+6)(x-2) = 

 

(3x+6)(3x-6)*

 

a+